Analysis on Free Video Call Applications Reliability as a Tool a case study of Online Islamic Matrimony - Tjokronolo, Sigit Prianto; Mohammad, Anggia Dyarini (Swiss German University, 2015)
The internet era has been improved so much over this past decade; wherepeople can easily get connected without having to consider distancebetween different locations. The way people communicate also haschanged from texting using conventional letter or SMS, to audio usingphone call and now video call where we can see and hear the person whowe talk to. Due to distance problem, nowadays some people prefer to useOnline Video Call to perform weddings. Although some Moslems are stilldebating the validity of an online matrimony where some Islamic scholarsagree by considering certain condition while some others disagree, thispaper won’t be discussing about the debated issue. This paper will only befocused on the video call application reliability in order to have a validonline Islamic matrimony. The comparison will be using free video callapplications such as Skype, Google Hang-out and Facebook Video Call